Molecular Response to Imatinib and Its Correlation with mRNA Expression Levels of Imatinib Influx Transporter (OCT1) in Indian Chronic Myeloid Leukemia Patients - Chhikara, S (Asian Pac J Cancer Prev, 2017)
BACKGROUND AND OBJECTIVES: Imatinib mesylate is approved for the treatment of Chronic Myeloid Leukemia (CML). About 20% of patients with CML do not respond to treatment with Imatinib either initially or because of acquired resistance. In addition to mutated BCR-ABL1 kinase, the organic cation transporter1 (OCT1, encoded by SLC22A1) has been considered to contribute to Imatinib resistance in patients with chronic myeloid leukemia (CML). OCT1 has been reported to be the main influx transporter involved in Imatinib uptake into CML cells. To date, only a few studies have been reported on involvement of influx transporters in development of Imatinib resistance. Therefore this study was aimed to determine the expression level of Imatinib uptake transporter (OCT1) in CML patients and to correlate this level with molecular response. METHODS: One hundred fifty eight patients on Imatinib were considered for gene expression analysis study for OCT1 gene. Total RNA was extracted from peripheral blood mononuclear cells. Complementary DNAs (cDNAs) were synthesized and Real Time Polymerase Chain Reaction (RQ-PCR) was performed. RESULTS: High OCT1 expression was present in 81 (51.8%) patients and low OCT1 expression was in 77 (48.7%) patients. Low Sokal risk score group have a significantly high OCT1 expression (p=0.048). The rate of molecular response was higher in those with high OCT1 expression than in those with low OCT1 expression (p=0.05). Both event-free survival and median overall survival were significantly shorter in patients with low OCT1 expressions when compared to the patients with high OCT1 expression (p=0.03 and p=0.05). CONCLUSIONS: Our findings demonstrated that the mRNA expression level of OCT1 was significantly correlated with molecular response in CML patients. Based on these findings, present study believes that the pre-therapeutic higher expression of OCT1 may help to predict response to imatinib therapy in CML patients.